Dietary intake assessment in children with cystic fibrosis using 3-day food diaries: a single-centre study - Gaschignard, Margaux; Beaufils, Fabien; Gallet, Pauline; Clouzeau, Haude; Menard, Joris; Costanzo, Aurélie; Nouard, Lucie; Delhaes, Laurence; Tetard, Candice; Lamireau, Thierry; Fayon, Michael; Bui, Stéphanie; et al. (Frontiers in Pediatrics, 2023)
Background: Malnutrition is both a feature and major cause of morbidity in cystic fibrosis (CF). Therefore, nutritional management is an essential element of patient care. In 2016, an international guideline for nutritional management in patients with CF was published. In light of these recommendations, the aim of this study was to investigate the dietary intake of children with CF at the University Hospital of Bordeaux. Methods: We conducted a retrospective study at the Paediatric CF Centre of the University Hospital of Bordeaux. Patients aged 2-18 years with CF who completed a 3-day food diary at home between January 2015 and December 2020 were included. Results: A total of 130 patients, with a median age of 11.8 (interquartile range [IQR]: 8.3; 13.4) years, were included. The median Z-score for BMI was -0.35 (IQR: -0.9; 0.2) and 20% of the patients had a Z-score for BMI <-1. Recommended total energy intakes were achieved in 53% of the patients, particularly those with nutritional support. Recommended protein intake was met in 28% of the cases, while fat and carbohydrate intakes were met in 54%. Vitamin and micronutrient levels were normal in 80% of the patients, with the exception of vitamin K, which was within the therapeutic range in only 42% of the cases. Conclusion: Recommended nutritional targets are difficult to achieve in patients with CF, and providing nutritional support during follow-up remains a challenge.